Red rural, blue rural? Presidential voting patterns in a changing rural America. (September 2015) - Scala, Dante J.; Johnson, Kenneth M.; Rogers, Luke T.
Abstract: This paper examines individual and aggregate data to document the growing political diversity in rural America. This political diversity is evident in the various economies within rural America. The new rural economy is reflected in recreational counties, where natural and built amenities combined with the provision of services to residents and visitors are the basis for the local economy. Residents of recreational counties tend to be more liberal than their rural peers on a variety of political issues, and supported Barack Obama at significantly higher levels in 2008 and 2012. In contrast, in regions dominated by the old rural economy of farming, political views are more conservative and there is far less support for Democrats in general and President Obama in particular. An analysis of survey data combined with multivariate spatial regression analysis demonstrates that these differences between the old and new rural economy persist even when a variety of demographic, economic, social and geographic variables are controlled.